1997
DOI: 10.2166/wst.1997.0414
|View full text |Cite
|
Sign up to set email alerts
|

Lab-scale evaluations on formation of products of incomplete combustion in hazardous waste incineration: influence of process variables

Abstract: Laboratory investigations have been carried out to study the influence of process failure modes on organics emission during the incineration of hazardous sludge. The thermal, temporal and fuel-oxidant mixing failure modes were tested. They were simulated by holding the first combustion temperature at 400°C and varying the after-burning one between 600 and 1100°C, the after-burning residence time between 1 and 3 s and the excess air between 30 and 160%. Results showed that the thermal failure mode is the most i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Among the simple aromatics, benzene is the most abundant because of its high thermal stability which, as is already known [19,20], once formed, is degraded thermally very slowly. The benzene thermal profiles (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Among the simple aromatics, benzene is the most abundant because of its high thermal stability which, as is already known [19,20], once formed, is degraded thermally very slowly. The benzene thermal profiles (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Further research carried out by other scientists [11][12][13][14] proved the presence of more than 350 chemical (organic) compounds of various types in flue gases from waste incineration plants in concentrations greater than 5 g/m 3 .…”
Section: Mechanism Of Dioxin Formation In Thermal Processesmentioning
confidence: 99%
“…The result of these reactions, which proceed outside the combustion zone, is the presence of pollutants in the flue gas, among others such as (Eduljee, 1994 Subsequent studies conducted by other researchers (Wienecke et al, 1995, Jay & Stieglitz, 1995, Mascolo et al, 1997, Trenholm 1998 showed the presence of more than 350 different types of chemical compounds (organic) in the flue gases from the waste incineration plants in concentrations above 5 µg/m 3 . Similar results were obtained for burning of wood and other biomass.…”
Section: Products Of Incomplete Combustionmentioning
confidence: 99%